Determinants of Growth in Prescription Drug Spending Using 2010–2019 Health Insurance Claims Data - Lee, HyeYeong; Park, Dahye; Kim, Dong-Sook (Frontiers in Pharmacology, 2021)
Background: Despite policies to manage prescription drug spending and ensure accessibility in South Korea, prescription drug spending has continued to rise. Using nationwide claims data, this study analyzed trends in total pharmaceutical expenditures and pharmaceutical expenditures by drug classification. Methods: We conducted study using national health insurance claims database from 2010 to 2019. We conducted a retrospective population-based study using the Korean national health insurance claims database from January 2010 through December 2019. Pharmaceuticals were categorized into new drugs, continued drugs, and abandoned drugs. Prescription drug spending was calculated using the components of price and quantity by individual products. Results: Total pharmaceutical expenditures increased by 54.2% from 2010 to 2019 (from USD 11.3 billion to USD 17.4 billion). The average annual growth rate was 4.9% overall (4% for continued drugs, -3.5% for the price of drugs, 6.5% for the quantity of drugs, and 1% for mixed effects, a measure of changes in drug treatment patterns). The trends were generally consistent. Particularly sharp increases in expenditures were found for groups L (antineoplastic and immune-modulating agents), C (cardiovascular system drugs), and A (metabolism drugs). Conclusion: Since increased prescription drug spending was primarily driven by an increase in the quantity of drugs used, a consumer-focused policy to reduce drug use is necessary.